Gloss on the Judgment of the Court of Justice of the European Union of 9 November 2023, Staatsanwaltschaft Aachen, C-819/21 - Smarzewski, Marek Ryszard (Review of European and Comparative Law, 2025)
The subject of considerations undertaken in the paper is the judgment of CJEU of 9 November 2023, Staatsanwaltschaft Aachen, C-819/21. The commented judgment was issued in response to preliminary questions submitted by the Landgericht Aachen (Regional Court, Aachen). It primarily addresses the possibility to recognise and enforce a custodial sentence by a court of the executing state if there are grounds to believe that the conditions in the issuing state – at the time of the judgment to be enforced or subsequent judgments concerning it – are inconsistent with the fundamental right to a fair trial, in particular because the judicial system in the Member State in question has been found to be incompatible with the rule of law and has a specific, adverse effect on the convicted person in the proceedings. CJEU ruled that the application of an exceptional ground for refusal not expressly regulated in FD 2008/909 is possible after conducting two-step test developed in CJEU’s case law with respect to the procedure for enforcing an EAW. This position of CJEU does not deserve uncritical approval, even though it is essentially consistent with the CJEU’s approach to the significance of abstract and concrete deficiencies relating to fundamental rights, including those affecting the right to a fair trial, in relation to the principle of mutual recognition of judgments and the exceptional possibility of derogation from it. The solution developed in the judgment of 9 November 2023 fails to take into account the fundamental differences between the EAW procedure and that set out in FD 2008/909 and raises doubts as to its functionality.